Quantification and determination of antagonistic activity of bifidobacteria and lactobacilli in faeces of breast-fed and mixed-fed infants - Chutima Jittaprasatsin (Chulalongkorn University, 2011)
Thesis (M.Sc.) --Chulalongkorn University, 2008